2006
DOI: 10.1002/jmri.20702
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study of somatosensory‐implicated acupuncture points in stable somatosensory stroke patients

Abstract: Purpose: To assess differences in brain responses between stroke patients and controls to tactile and electrical acupuncture stimulation using functional MRI (fMRI). Materials and Methods:A total of 12 male, clinically stable stroke patients with left side somatosensory deficits, and 12 age-matched male control subjects were studied. fMRI was performed with two different paradigms; namely, tactile stimuli and electrical stimulation at acupuncture points LI4 and LI11 on the affected side of the body. fMRI data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 44 publications
2
66
0
Order By: Relevance
“…Five Chinese studies [61±65] found almost no significant differences between verum and sham, though two of them found greater activation intensity in the cerebellum or parietal lobe for verum acupuncture [61,62]. Among the three publications on patients, Schockert et al [20] found more activation in the motor area on stroke patients during acupuncture while Li et al [17] found more activation in the somatosensory and motor areas with a control, brushing stimulation on stroke patients. In patients with Parkinson's disease Chae et al [18] showed that acupuncture was associated with more activation than covert cutaneous stimulation in the motor area, basal ganglia, visual and higher cognitive area; and more activation in the motor, visual, higher cognitive areas and limbic system, compared to overt cutaneous stimulation.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five Chinese studies [61±65] found almost no significant differences between verum and sham, though two of them found greater activation intensity in the cerebellum or parietal lobe for verum acupuncture [61,62]. Among the three publications on patients, Schockert et al [20] found more activation in the motor area on stroke patients during acupuncture while Li et al [17] found more activation in the somatosensory and motor areas with a control, brushing stimulation on stroke patients. In patients with Parkinson's disease Chae et al [18] showed that acupuncture was associated with more activation than covert cutaneous stimulation in the motor area, basal ganglia, visual and higher cognitive area; and more activation in the motor, visual, higher cognitive areas and limbic system, compared to overt cutaneous stimulation.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Needle studies describe consistently the involvement of the sensory cortex. 13,40,41,[52][53][54] As the lowintensity laser has non-nociceptive properties, activation of the primary somatosensory cortex was not recorded for all acupoints except LR 8, which was stimulatory of primary sensory and motor cortices. The significance of this is not known.…”
Section: Laterality Of Stimulation and Sensorimotor Cortical Stimulationmentioning
confidence: 97%
“…Due to an increase in its popularity, there has been a recent diversification of acupuncture research away from the more traditional study of pain 3 into the examination of the role of acupuncture in mental disorders. [4][5][6][7][8][9][10][11][12][13] The first foray into the use of acupuncture in the treatment of depression was the investigatory work on electroacupuncture. 6,7 These earlier studies were followed by clinical studies from 1998 when the use of manual needle acupuncture in depression was revisited.…”
Section: Introductionmentioning
confidence: 99%
“…To measure the effects of acupuncture with fMRI, studies have been conducted on healthy participants [12][13][14][15], indicating that each acupoint has its own specific effect, and on patients with diseases, showing that acupuncture is able to improve the symptoms of patients [16][17][18]. However, to our knowledge, there has so far been no fMRI study that directly measures and compares brain activity in response to acupuncture stimulating manipulation in healthy participants to those of patients with Parkinson's disease (PD).…”
Section: Introductionmentioning
confidence: 99%